Risk of bone fractures after the diagnosis of adrenal adenomas: a population-based cohort study. Issue 4 (April 2021) - Li, Dingfeng; Kaur, Ravinder Jeet; Zhang, Catherine D; Ebbehoj, Andreas; Singh, Sumitabh; Atkinson, Elizabeth J; Achenbach, Sara J; Rocca, Walter; Khosla, Sundeep; Bancos, Irina
Abstract : Objective: Several small studies reported increased prevalence and incidence of asymptomatic vertebral fractures in patients with non-functioning adrenal adenomas and adenomas with mild autonomous cortisol secretion. However, the risk of symptomatic fractures at vertebrae, and at other sites remains unknown. Our objective was to determine the prevalence and incidence of symptomatic site-specific fractures in patients with adrenal adenomas. Design: Population-based cohort study, Olmsted County, Minnesota, USA, 1995–2017. Methods: Participants were the patients with adrenal adenoma and age/sex-matched referent subjects. Patients with overt hormone excess were excluded. Main outcomes measures were prevalence and incidence of bone fractures. Results: Of 1004 patients with adrenal adenomas, 582 (58%) were women, and median age at diagnosis was 63 years (20–96). At the time of diagnosis, patients had a higher prevalence of previous fractures than referent subjects (any fracture: 47.9% vs 41.3%, P = 0.003, vertebral fracture: 6.4% vs 3.6%, P = 0.004, combined osteoporotic sites: 16.6% vs 13.3%, P = 0.04). Median duration of follow-up was 6.8 years (range: 0–21.9 years). After adjusting for age, sex, BMI, tobacco use, prior history of fracture, and common causes of secondary osteoporosis, patients with adenoma had hazard ratio of 1.27 (95% CI: 1.07–1.52) for developing a new fracture during follow up when compared to referent subjects. Conclusions: Patients with adrenal adenomas have higher prevalence of fractures at the time of diagnosis and increased risk to develop new fractures when compared to referent subjects.